Community Knowledge and Actions in Controlling Dengue Hemorrhagic Fever - Dwi Pristiany; Wanti Wanti; Johanes Pitreyadi Sadukh; Oktofianus Sila; Agustina Agustina (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Dengue Haemorrhagic Fever (DHF) is an endemic disease in Indonesia, including in NTT Province. The city of Kupang as the capital of NTT Province is also an endemic area for dengue fever and almost every year there are deaths due to dengue fever. This study aims to determine the knowledge and actions of the community in controlling DHF in Kupang City in 2020. This descriptive study was conducted in Kupang City, NTT Province with the research variables being knowledge and action in controlling DHF. The population in this study is all people who live in Kupang City, with the research sample being respondents who are willing to take online surveys and submit answers on google form, which are 111 people. Primary data was obtained by distributing online questionnaires in google form via IG, FB, WA and email. The collected data is processed and analyzed descriptively by calculating the number and percentage of respondents' answers for each research variable sought. This study found that the community's knowledge about DHF and its control was mostly in the sufficient category (67%), and knowledge about House Jumantik was mostly in the poor category (56%). There are still some DHF control measures that are still lacking, namely the use of mosquito nets during naps, installation of wire netting in home ventilation, reuse of used goods, planting of mosquito repellent plants, cleaning the yard at least once a week and spreading fish larvae eater in a water container. For this reason, there is still a need for health promotion related to DHF and its control, including when mosquitoes suck blood, as well as ways that can be done in eradicating and controlling DHF in Liliba Village, Kupang City.